2019
DOI: 10.3390/atmos10120792
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Green Roofs on the Parameters of the Environment in Urban Areas—Review

Abstract: This study presents the results of a review of publications conducted by researchers in a variety of climates on the implementation of ‘green roofs’ and their impact on the urban environment. Features of green roofs in urban areas have been characterized by a particular emphasis on: Filtration of air pollutants and oxygen production, reduction of rainwater volume discharged from roof surfaces, reduction of so-called ‘urban heat islands’, as well as improvements to roof surface insulation (including noise reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 101 publications
0
12
0
Order By: Relevance
“…Some residential and commercial cooking activities are still using solid fuels which creates health hazards similar to PM 2.5 . Green Roof Technologies can reduce the risk of PM 2.5 in a significant way [ 37 ] and are highly suitable and sustainable with respect to the economic, socio-economic and housing properties of Dhaka city.…”
Section: Resultsmentioning
confidence: 99%
“…Some residential and commercial cooking activities are still using solid fuels which creates health hazards similar to PM 2.5 . Green Roof Technologies can reduce the risk of PM 2.5 in a significant way [ 37 ] and are highly suitable and sustainable with respect to the economic, socio-economic and housing properties of Dhaka city.…”
Section: Resultsmentioning
confidence: 99%
“…A drainage layer for each model was made: for model 1, in the form of drainage pipe, and for model 2, in the form of a 2-cm layer of gravel fraction of 1–1.5 cm (allowing excess rainwater to go to the vertical discharge pipe) (Suszanowicz 2018 ). For the extensive model, a layer of soil of 15 cm was used, and a layer of 35 cm was used for the intensive roof (Suszanowicz and Kolasa-Więcek 2019 ). In both cases, the soil mixtures were prepared in accordance with the recommendations of the German Landscape Research, Development, and Construction Society (Forschungsgesellschaft Landschaftsentwicklung Landschaftsbau—FLL) (Lösken et al 2018 ; Kaiser et al 2019 ) and DAFA (Association of Flat Rooftops and Façade Contractors) (Lundholm 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…• structural-planning functions (possibility of more optimal use of densely built spaces). 8 Ambient air temperature during summer months decreased around buildings with an extensive green roof with an organic based substrate 10-15 cm depths (Sedum plants). 3 Onmura et al (2001) found a 4-5 C reduction in temperature resulting directly from the green roof vegetation, and Lundholm et al (2010) found that green roofs cooled the surface 3 C over vegetation-free substrate only controls, as well as more than 16 C over asphalt roof surfaces.…”
Section: Introductionmentioning
confidence: 99%